Simplifique a fraçao:
x²-1 . 3x-6
x²-2x. 4x+4
Usuário anônimo:
não está entre parênteses?
Soluções para a tarefa
Respondido por
0
Sem parênteses:
= x² - 1.3x - 6
= x² - 3x - 6
--------------------------------------------
= x² - 2x.4x+4
= x² - 8x² + 4
= - 7x² + 4
-------------------------------------------------------
Com parênteses:
= (x² - 1) . (3x - 6)
3 2
= 3x - 6x - 3x +6
=======================
= (x² - 2x). (4x + 4)
= 4x³ + 4x² - 8x² - 8x
= 4x³ - 4x² - 8x
= 4x.(x² - x - 2)
= x² - 1.3x - 6
= x² - 3x - 6
--------------------------------------------
= x² - 2x.4x+4
= x² - 8x² + 4
= - 7x² + 4
-------------------------------------------------------
Com parênteses:
= (x² - 1) . (3x - 6)
3 2
= 3x - 6x - 3x +6
=======================
= (x² - 2x). (4x + 4)
= 4x³ + 4x² - 8x² - 8x
= 4x³ - 4x² - 8x
= 4x.(x² - x - 2)
Perguntas interessantes
Matemática,
1 ano atrás
Geografia,
1 ano atrás
Filosofia,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Matemática,
1 ano atrás
Artes,
1 ano atrás